Multifunctional injectable hydrogels and their preparation, use
Patent Information
- Application Number
- CN202611067922.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-09-29
AI Technical Summary
目前,尚未见相关报道
[0021](1)本申请首先提供了GO@FE在制备多功能可注射水凝胶中的应用;与采用未修饰的氧化石墨烯制备的OPQ/GO水凝胶相比,采用GO@FE制备的OPQ/GO@FE水凝胶,光热性能和力学性能均实现了显著提升,技术效果显著,对于后续的理论研究和实际应用均具有重要的意义。
Smart Images

Figure CN122828172A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biomaterials and relates to a hydrogel and its preparation method. Specifically, it relates to a multifunctional injectable hydrogel with cfDNA removal, anti-oxidation and photothermal oxygen controlled release, as well as its preparation and application. Background Technology
[0002] The impaired healing of chronic diabetic wounds stems from the interplay of multiple pathological factors and is one of the most common and difficult-to-treat complications of diabetes. This is because: (1) persistent hyperglycemia leads to the accumulation of advanced glycation end products (AGEs), triggering dysregulation of the inflammatory response; (2) microvascular complications caused by diabetes result in insufficient tissue perfusion and local hypoxia, weakening the effective delivery of nutrients and oxygen; (3) the high-glucose microenvironment also induces mitochondrial dysfunction and NADPH oxidase activation, promoting excessive accumulation of reactive oxygen species (ROS) and causing oxidative stress damage; (4) immune dysfunction caused by diabetes makes the wound susceptible to bacterial invasion and the formation of biofilms. These mechanisms are interconnected, forming a vicious cycle that severely hinders the healing process of chronic diabetic wounds. In addition, studies have found that under the stimulation of high glucose, ROS and inflammatory factors, neutrophils are overactivated, releasing cell-free DNA (cfDNA), histones and granule proteins, resulting in the formation of a large number of extracellular neutrophil traps (NETs); this is also one of the key factors driving chronic inflammation of diabetic wounds and hindering healing.
[0003] Currently, common clinical treatments for diabetic wounds include debridement, antibacterial dressings, negative pressure wound therapy, and growth factor therapy. However, on the one hand, existing treatments often target single pathological stages and lack the ability to synergistically regulate multiple obstacles. For example, while silver ion dressings have good antibacterial properties, they cannot eliminate NETs or alleviate oxidative stress; alginate dressings can maintain a moist wound environment but are insufficient to improve tissue hypoxia. On the other hand, the microenvironment of diabetic wounds exhibits dynamic heterogeneity: the inflammatory phase is dominated by cfDNA accumulation and bacterial infection, while the proliferative phase is characterized by impaired angiogenesis and cell function. This phased characteristic necessitates treatment strategies with dynamic responsiveness and adaptability.
[0004] Injectable hydrogels have shown promise in the treatment of diabetic wounds due to their advantages such as filling irregular wounds, achieving sustained drug release, and mimicking the extracellular matrix. Addressing the aforementioned pathological characteristics, hydrogels used for chronic diabetic wounds need to possess the functions of clearing cfDNA, regulating macrophage polarization, scavenging ROS, and controlling oxygen release, while simultaneously exhibiting antibacterial and biocompatibility—inhibiting pathogenic bacteria such as Staphylococcus aureus and Pseudomonas aeruginosa, as well as biofilm formation, without interfering with the normal wound repair process. Currently, using quaternized chitosan and oxidized pullulan as precursors to form injectable hydrogels in situ under physiological conditions via a Schiff base reaction is a common strategy for constructing wound dressings with antibacterial, self-healing, and highly absorbent properties. This preparation method involves mild reaction conditions, requiring no external cross-linking agents or organic solvents; and the resulting hydrogel exhibits good biocompatibility, injectability, self-healing ability, and wet adhesion, and can be loaded with antibacterial agents or growth factors to promote skin wound healing.
[0005] However, as mentioned earlier, the microenvironment of chronic diabetic wounds is highly complex, exhibiting multiple pathological challenges, including excessive accumulation of cell-free DNA (cfDNA) released from extracellular neutrophil traps (NETs), oxidative stress damage caused by excessive reactive oxygen species (ROS) production, severe tissue hypoxia due to microvascular complications, and bacterial susceptibility and biofilm formation caused by immune dysfunction. Existing Schiff base cross-linked hydrogels based on quaternized chitosan and oxidized pullulan (QCS / OPL) cannot efficiently remove ROS, nor do they possess the oxygen delivery capacity to alleviate wound hypoxia, and research on their cfDNA removal effects is lacking. Therefore, these hydrogels can only provide physical coverage, moisture absorption, and basic antibacterial effects, failing to simultaneously intervene in multiple key aspects of the vicious cycle of "inflammation-oxidative stress-hypoxia-infection," resulting in limited therapeutic efficacy for chronic diabetic wounds.
[0006] In summary, constructing a multifunctional injectable hydrogel capable of synergistically achieving cfDNA clearance, macrophage phenotypic regulation, ROS clearance, controlled oxygen release, and broad-spectrum antibacterial activity is of significant clinical importance for overcoming the bottleneck in the treatment of diabetic chronic wounds. Currently, no relevant reports have been found. Summary of the Invention
[0007] To address the problems existing in the use of injectable hydrogels for the treatment of chronic diabetic wounds in the prior art, this invention provides an injectable hydrogel. The multifunctional injectable hydrogel uses a Schiff base crosslinked hydrogel of quaternized chitosan and oxidized pullulan as a base, and incorporates an appropriate amount of EGCG-Fe. 3+ It is obtained by modifying graphene oxide GO@FE and oxyhemoglobin HbO2, and has multiple functions such as cfDNA removal, anti-oxidation, photothermal controlled oxygen release and antibacterial properties. It can effectively promote the healing of refractory diabetic wounds and has important application value and social significance.
[0008] The technical solution of this invention:
[0009] This application first provides EGCG-Fe 3+ The application of modified graphene oxide (GO@FE) in the preparation of multifunctional injectable hydrogels, wherein the injectable hydrogels are Schiff base crosslinked hydrogels (OPQ hydrogels) based on quaternized chitosan and oxidized pullulan. The content of GO@FE in the multifunctional injectable hydrogel is 0.9~4.0 mg / ml; the EGCG:Fe content in GO@FE is... 3+ The molar ratio of GO to graphene oxide (GO) is 1:8:20 to 1:3:7. Although graphene oxide (GO) is a common photothermal conversion material, the inventors unexpectedly discovered that Schiff base crosslinked hydrogels prepared using GO@FE (OPQ / GO@FE hydrogel) exhibit significantly better photothermal performance than hydrogels prepared using unmodified graphene oxide (OPQ / GO hydrogel), achieving an unexpected technical effect. Furthermore, at the aforementioned molar ratio, both OPQ / GO@FE hydrogels can heat up to above 40°C under near-infrared irradiation, indicating good photothermal stability and applicability. Moreover, compared to the basic OPQ hydrogel, the mechanical strength of the OPQ / GO hydrogel with the introduction of unmodified graphene oxide is reduced. However, the mechanical strength of the OPQ / GO@FE hydrogel with the introduction of GO@FE is increased compared to the OPQ / GO hydrogel, effectively improving the mechanical properties of the hydrogel. In summary, the introduction of GO@FE into Schiff base crosslinked hydrogels has resulted in a significant improvement in both photothermal and mechanical properties. This is a discovery and the first public disclosure of this technology, demonstrating remarkable technical effectiveness and holding significant importance for subsequent theoretical research and practical applications.
[0010] Preferably, the GO@FE is prepared by the following method: (1) a graphene oxide (GO) dispersion is prepared and ultrasonically dispersed to ensure uniform dispersion; wherein the concentration of the graphene oxide dispersion is 0.05-0.3 mg / ml; the ultrasonic dispersion is specifically performed by ultrasonic cleaning at 40 Hz for 25-50 min. (2) Under room temperature and light-protected conditions, EGCG is added and stirred for 25-45 min until the modification is complete, then ferric chloride hexahydrate is added and stirred for 2-5 min until the modification is complete. After centrifugation and washing, a precipitate is obtained, which is GO@FE. The centrifugation is specifically performed by centrifugation at 2-8℃ and 12000-13000 r for 5-10 min.
[0011] This application also provides a multifunctional injectable hydrogel based on the aforementioned applications, wherein the injectable hydrogel is a Schiff base crosslinked hydrogel of quaternized chitosan and oxidized pullulan, and the injectable hydrogel further comprises EGCG-Fe3+ The invention relates to modified graphene oxide (GO@FE) and oxyhemoglobin (HbO2); wherein the content of GO@FE is 0.9-4.0 mg / ml, and the content of oxyhemoglobin (HbO2) is 14.5-20.0 mg / ml. Oxyhemoglobin (HbO2), as a natural oxygen carrier, possesses the characteristic of reversibly releasing oxygen at 40–41°C. The multifunctional injectable hydrogel described in this application is a Schiff base cross-linked hydrogel (OPQ / GO@FE hydrogel) incorporating GO@FE, possessing excellent and stable photothermal properties, capable of heating to above 40°C under near-infrared irradiation, meeting the demand for oxygen release from HbO2 under light conditions. Therefore, the multifunctional hydrogel described in this application, based on the combination of photothermal properties and HbO2, achieves reversible binding and on-demand release of oxygen, potentially alleviating hypoxia in wounds, with significant technical effects. It should be noted that the hydrogel is obtained by mixing two liquid components and allowing them to stand for a period of time; the contents of GO@FE and HbO2 in the multifunctional hydrogel described in this application are their contents in the liquid system.
[0012] The Schiff base crosslinked hydrogel is obtained by reacting a quaternized chitosan solution and an oxypullulan solution at a volume ratio of 2:1 to 1:2; the concentration of the oxypullulan solution is 20-40 mg / ml, and the concentration of the quaternized chitosan solution is 30-90 mg / ml. The quaternized chitosan solution and / or the oxypullulan solution contain appropriate amounts of graphene oxide (GO@FE) and / or oxyhemoglobin (HbO2). The introduced graphene oxide (GO@FE) and oxyhemoglobin (HbO2), along with the quaternized chitosan solution and the oxypullulan solution forming the hydrogel matrix, can be arbitrarily combined. As long as the content of graphene oxide (GO@FE) and oxyhemoglobin (HbO2) in the final hydrogel is appropriate, the aforementioned controlled oxygen release effect can be achieved.
[0013] Furthermore, the multifunctional hydrogel described in this application also has the following functions: (1) scavenging cfDNA - through the electrostatic adsorption of negatively charged cfDNA by the cationic groups of quaternized chitosan (QCS), which is not disclosed in the prior art, blocking the TLR-9 / NF-κB inflammatory pathway; (2) regulating macrophage polarization - loading bioactive molecules such as EGCG to promote the transformation of macrophages from M1 to M2 type and regulate the NF-κB and Nrf2 signaling pathways; (3) scavenging ROS - using EGCG to scavenge free radicals, chelate metal ions and activate endogenous antioxidant enzymes; (5) antibacterial and biocompatibility - inhibiting pathogenic bacteria such as Staphylococcus aureus and Pseudomonas aeruginosa and biofilm formation, while not interfering with the normal wound repair process.
[0014] In summary, the multifunctional injectable hydrogel described in this application possesses multiple functions such as cfDNA removal, anti-oxidation, photothermal controlled oxygen release, and antibacterial properties through the synergistic effect of its components. It is expected to achieve joint regulation of multiple pathological disorders in diabetic chronic wounds, providing a safe, efficient, and intelligent new material for wound repair in clinical practice.
[0015] This application also provides a method for preparing the multifunctional injectable hydrogel as described above, comprising the following steps:
[0016] (1) Prepare an oxidized pullulan polysaccharide solution with a concentration of 20-40 mg / ml, add an appropriate amount of GO@FE and HbO2 in PBS solution to obtain component A; the concentration of GO@FE in component A is 0.9-4.0 mg / ml, and the content of oxyhemoglobin HbO2 is 14.5-20 mg / ml.
[0017] (2) Prepare a quaternized chitosan solution with a concentration of 30-90 mg / ml, add an appropriate amount of GO@FE and HbO2 in PBS solution to obtain component B; the concentration of GO@FE in component B is 0.9-4.0 mg / ml, and the content of oxyhemoglobin HbO2 is 14.5-20 mg / ml.
[0018] (3) Mix component A and component B in a volume ratio of 2:1 to 1:2, let stand for 0.5 to 5 minutes, and form gel OPQH / GO@FE in situ.
[0019] As previously mentioned, graphene oxide (GO@FE) and oxyhemoglobin (HbO2), along with the quaternized chitosan solution and pullulan oxidase solution forming the hydrogel matrix, can be arbitrarily combined. However, the preparation method provided in this application involves adding GO@FE and oxyhemoglobin (HbO2) of equal concentration to components A and B. This ensures that regardless of the volume ratio of components A and B, the content of graphene oxide (GO@FE) and oxyhemoglobin (HbO2) in the final hydrogel product remains unaffected, further preserving the controlled oxygen release function. This significantly simplifies the computational process and experimental procedures, which is of great significance for practical production.
[0020] Technical effects of the present invention:
[0021] (1) This application first provides the application of GO@FE in the preparation of multifunctional injectable hydrogels; compared with OPQ / GO hydrogels prepared with unmodified graphene oxide, OPQ / GO@FE hydrogels prepared with GO@FE have significantly improved photothermal and mechanical properties, and the technical effect is significant, which is of great significance for subsequent theoretical research and practical application.
[0022] (2) This application also provides a multifunctional injectable hydrogel based on the aforementioned application. The injectable hydrogel not only achieves reversible binding and on-demand release of oxygen by introducing GO@FE and HbO2, which is expected to alleviate the hypoxia of the wound, but also has multiple functions such as cfDNA removal, anti-oxidation, photothermal controlled oxygen release and antibacterial properties, filling the gap in the prior art.
[0023] (3) This application also provides a method for preparing the multifunctional injectable hydrogel, which simplifies the complexity of the calculation process and the experimental operation, and is of great significance for actual production. Attached Figure Description
[0024] Appendix Figure 1 The FT-IR spectrum of GO@FE in Example 4 ( Figure 1 a) and a comparison of the TEM images of GO and GO@FE ( Figure 1 b).
[0025] Appendix Figure 2 FT-IR spectra of oxidized pullulan and pullulan in Example 5 (a) and 1 H NMR spectrum (b).
[0026] Appendix Figure 3 This is a photograph showing the injectability of the OPQH / GO@FE gel in Example 8.
[0027] Appendix Figure 4 The image shows the self-healing results of the OPQH / GO@FE gel in Example 8; where (a) is a picture of the self-healing process and (b) is a graph of the elastic modulus at 1% strain and 1000% strain.
[0028] Appendix Figure 5 The figure shows the oxygen release capacity of the OPQH / GO@FE gel in Example 8; (a) shows the oxygen release capacity of PBS, OPQH / GO@FE NIR(-), and OPQH / GO@FE NIR(+); (b) shows the oxygen cycle release of OPQH / GO@FE after five NIR irradiation switching cycles.
[0029] Appendix Figure 6 The image shows the cfDNA removal ability of the OPQH / GO@FE gel prepared in Example 5.
[0030] Appendix Figure 7 The images show gelation patterns (a) of the OPQH gel prepared in Comparative Example 2, the OPQH / GO gel prepared in Comparative Example 1, and the OPQH / GO@FE gel prepared in Example 5, and (b) of the OPQH / GO@FE gel.
[0031] Appendix Figure 8 Rheological properties of the OPQH gel prepared in Comparative Example 2, the OPQH / GO gel prepared in Comparative Example 1, and the OPQH / GO@FE gel prepared in Example 5.
[0032] Appendix Figure 9 The first image shows the adhesion of OPQH / GO@FE in Example 9 (a), the second image shows the adhesion-displacement curves of the OPQH gel prepared in Comparative Example 2, the third image shows the OPQH / GO gel prepared in Comparative Example 1, and the fourth image shows the adhesion strength results (c).
[0033] Appendix Figure 10 The antioxidant results are shown in the figure for the OPQH gel prepared in Comparative Example 2, the OPQH / GO gel prepared in Comparative Example 1, and the OPQH / GO@FE gel prepared in Example 5; where (a) is the scavenging rate of DPPH and (b) is the scavenging rate of hydroxyl radicals.
[0034] Appendix Figure 11 The photothermal curves (a) of the OPQH gel prepared in Comparative Example 2, the OPQH / GO gel prepared in Comparative Example 1, the OPQH / GO@FE gel prepared in Example 5, and PBS under NIR irradiation and the photothermal stability diagram (b) of the OPQH / GO@FE gel after five NIR irradiation switching cycles are shown.
[0035] Appendix Figure 12 The antibacterial activity results of the OPQH gel prepared in Comparative Example 2, the OPQH / GO gel prepared in Comparative Example 1, and the OPQH / GO@FE gel prepared in Example 5 are shown in the figure; (a) is a plate coating photograph of typical agar culture of Staphylococcus aureus and Escherichia coli; (b) is the antibacterial rate of the gel against Staphylococcus aureus and Escherichia coli.
[0036] Appendix Figure 13 The hemolytic results are shown in the graphs for the OPQH gel prepared in Comparative Example 2, the OPQH / GO gel prepared in Comparative Example 1, and the OPQH / GO@FE gel prepared in Example 5. Among them, (a) is the color of the supernatant after centrifugation for each group, and (b) is a bar chart of the hemolysis rate.
[0037] Appendix Figure 14 The graph shows the cell survival rates of HUVEC cells (a), RAW macrophages (b), and L929 cells (c) prepared with the OPQH gel prepared in Comparative Example 2, the OPQH / GO gel prepared in Comparative Example 1, and the OPQH / GO@FE gel prepared in Example 5.
[0038] Appendix Figure 15The images show the fluorescence results of staining HUVEC and L929 cells with live and dead cells using the OPQH gel prepared in Comparative Example 2, the OPQH / GO gel prepared in Comparative Example 1, and the OPQH / GO@FE gel prepared in Example 5. Detailed Implementation
[0039] The present invention will be further described below with reference to the embodiments.
[0040] Example 1: EGCG-Fe 3+ Preparation of modified graphene oxide (GO@FE)
[0041] (1) Prepare a graphene oxide (GO) dispersion and perform ultrasonic dispersion treatment to ensure that it is fully and uniformly dispersed; wherein, the concentration of the graphene oxide dispersion is 0.3 mg / ml; the ultrasonic dispersion treatment is specifically performed by ultrasonic cleaning in a 40 Hz ultrasonic cleaner for 40 min.
[0042] (2) Under room temperature and light-protected conditions, EGCG was added and stirred for 40 min until complete modification. Then, ferric chloride hexahydrate was added and stirred for 5 min until complete modification. After centrifugation and washing, the precipitate was obtained, which was GO@FE. Wherein, EGCG:Fe 3+ The molar ratio of GO is 1:4:10, and the centrifugation process is specifically: centrifugation at 4℃ and 12000r for 10min.
[0043] Example 2: EGCG-Fe 3+ Preparation of modified graphene oxide (GO@FE)
[0044] (1) Prepare a graphene oxide (GO) dispersion and perform ultrasonic dispersion treatment to ensure that it is fully and uniformly dispersed; wherein, the concentration of the graphene oxide dispersion is 0.05 mg / ml; the ultrasonic dispersion treatment is specifically performed by ultrasonic cleaning in a 40 Hz ultrasonic cleaner for 25 min.
[0045] (2) Under room temperature and light-protected conditions, EGCG was added and stirred for 25 minutes until complete modification. Then, ferric chloride hexahydrate was added and stirred for 2 minutes until complete modification. After centrifugation and washing, the precipitate was obtained, which was GO@FE. Wherein, EGCG:Fe 3+ The molar ratio of GO is 1:8:20, and the centrifugation process is specifically: centrifugation at 8°C and 13000r for 5 minutes.
[0046] Example 3: EGCG-Fe 3+ Preparation of modified graphene oxide (GO@FE)
[0047] (1) Prepare a graphene oxide (GO) dispersion and perform ultrasonic dispersion treatment to ensure that it is fully and uniformly dispersed; wherein, the concentration of the graphene oxide dispersion is 0.2 mg / ml; the ultrasonic dispersion treatment is specifically performed by ultrasonic cleaning in a 40 Hz ultrasonic cleaner for 50 min.
[0048] (2) Under room temperature and light-protected conditions, EGCG was added and stirred for 30 minutes until complete modification. Then, ferric chloride hexahydrate was added and stirred for 4 minutes until complete modification. After centrifugation and washing, the precipitate was obtained, which was GO@FE. Wherein, EGCG:Fe 3+ The molar ratio of GO is 1:3:7, and the centrifugation process is specifically: centrifugation at 6°C and 12000r for 8 minutes.
[0049] Example 4: Characterization of GO@FE prepared in Examples 1-3
[0050] 1. Fourier transform infrared spectroscopy (FT-IR)
[0051] This embodiment first uses Fourier transform infrared spectroscopy to characterize the GO@FE prepared in Examples 1-3. By comparing the infrared spectra of unmodified graphene oxide (GO), the shifts, intensities, and peak shape changes of characteristic absorption peaks are analyzed to confirm the successful modification of the EGCG-Fe³⁺ complex on the GO surface. Unmodified GO is used as a blank control to evaluate the specificity and efficiency of the modification. The results are consistent. Example 1 is described in detail below.
[0052] Figure 1 a is the FTIR spectrum of GO@FE prepared in Example 1. Figure 1As shown in a, (1) compared with the control sample (unmodified GO), the O-H stretching vibration peak at 3000–3600 cm⁻¹ broadened and its intensity decreased. This may be due to the hydrogen bonding between the phenolic hydroxyl group of EGCG and the oxygen-containing group of GO, as well as the consumption of free O-H by the coordination reaction of Fe³⁺ with the hydroxyl group; (2) the intensity of the C=O peak at 1720 cm⁻¹ was significantly weakened, which may be attributed to the electrostatic adsorption and coordination bonding of Fe³⁺ with the carboxylate group on the GO surface. This electronic effect weakened the vibrational dipole moment of the C=O double bond; (3) the characteristic C-O peaks in the range of 1049–1362 cm⁻¹ decreased, while the epoxy structure peak at 400–600 cm⁻¹ completely disappeared. This may be attributed to the strong coordination reaction of Fe³⁺ with the epoxy group, which caused the C-O-C bridge bond to break and recombine; (4) while the peak at 1621 cm⁻¹ was significantly weakened. The broadening of the absorption peak at cm⁻¹ reflects the π-π stacking interaction between the aromatic ring of EGCG and the sp² conjugated domains of the carbon layer in GO, which alters the delocalized π-electron vibrational environment. In summary, hydrogen bonding and π-π stacking dominate the physical loading of EGCG, along with the Fe³⁺ coordination reaction, resulting in a synergistic loading on the GO surface. This demonstrates the successful modification of the EGCG-Fe³⁺ composite onto the GO surface, providing a structurally well-defined and stable precursor for subsequent antioxidant performance studies.
[0053] 2. Transmission electron microscopy (TEM)
[0054] In this embodiment, transmission electron microscopy (TEM) was used to observe the GO@FE prepared in Examples 1-3. The results were consistent. The following is a detailed description using Example 1 as an example. Figure 1 b is a TEM image of GO@FE prepared in Example 1. Figure 1 As shown in b, both GO (left image) and GO@FE (right image) exhibit the typical sheet morphology of graphene oxide, proving that EGCG and Fe 3+ It does not affect the morphology of graphene oxide. Further observation revealed obvious agglomeration on the surface of GO sheets, while GO@FE could spread uniformly, indicating that EGCG and Fe... 3+ The modification enhanced the dispersibility of GO@FE, which laid the foundation for the uniform dispersion of GO@FE in the gel matrix in the later stage.
[0055] Example 5: Preparation of a multifunctional injectable hydrogel
[0056] 1. Oxidized pullulan was prepared using a method described in the literature, as follows:
[0057] Weigh pullulan and dissolve it in deionized water to prepare a 10 mg / ml pullulan solution. Stir on a magnetic stirrer (35℃~40℃, 400~500 rpm) for 4 hours until the solid is completely dissolved. Then, mix the dissolved sodium periodate and pullulan in a 1:1 molar ratio at room temperature in the dark for 2 hours. Next, place the reaction solution into a dialysis bag with a molecular weight cutoff of 8~14 kDa and dialyze against deionized water for 3 days, changing the water every 6~12 hours. After dialysis, pre-freeze the solution at -20℃ for 20 hours, then freeze-dry it under vacuum at -70℃ for 48 hours to obtain a white, soft, foamy, plate-like substance, which is oxidized pullulan.
[0058] Using FT-IR and 1 ¹H NMR analysis of the chemical structures of oxidized pullulan (OP) and pullulan (Pullulan) is shown in the attached table. Figure 2 .like Figure 2 As shown in the FT-IR spectrum of a, oxidized pullulan exhibits a new peak at 1732 cm⁻¹ for the C=O stretching vibration of the aldehyde group, while natural polysaccharides do not show this absorption. This demonstrates that periodic acid selectively oxidizes vicinal diols (C2–C3 positions) to generate aldehyde groups, successfully preparing oxidized pullulan (OP) and providing active sites for Schiff base crosslinking. Figure 2 The ¹H NMR spectroscopy (b) showed an aldehyde proton signal at 9.12 ppm in the oxidation product, a peak absent in natural polysaccharides, further confirming the introduction of the aldehyde group. Simultaneously, the two original terminal proton peaks at 5.6–6.0 ppm merged into a single broad peak, attributed to a slight change in the chemical environment after oxidation, but without disruption of the glycosidic bond. The hydroxyl signal disappeared at 6.2–6.5 ppm, indicating oxidation to a carboxyl group or hydrogen-deuterium exchange with heavy water (D₂O baseline 4.79 ppm). These results consistently confirm the successful preparation of OP.
[0059] 2. The oxyhemoglobin (HbO2)-PBS solution was prepared using a method described in the literature, as follows:
[0060] Prepare a 60 mg / ml hemoglobin PBS solution. After complete dissolution, centrifuge (10000 rpm, 4℃, 10 min). Collect the supernatant in a 10 ml beaker, seal the beaker opening with plastic wrap leaving a small hole, and insert the tube of an oxygen generator into the small hole to purge the reaction solution with 70% oxygen for 5 hours to obtain the oxyhemoglobin HbO2-PBS solution. 。
[0061] 3. Assembly of OPQH / GO@FE injectable hydrogel
[0062] (1) Prepare an oxidized pullulan polysaccharide solution with a concentration of 40 mg / ml by dispersing an appropriate amount of GO@FE prepared in Example 1 and HbO2-PBS solution prepared in Step 2 of this Example to obtain component A; wherein component A contains GO@FE The concentration was 1 mg / ml, and the content of oxyhemoglobin (HbO2) was 15 mg / ml.
[0063] (2) Prepare a quaternized chitosan solution with a concentration of 70 mg / ml, add an appropriate amount of GO@FE prepared in Example 1 and HbO2-PBS solution prepared in step 2 of this Example and disperse them thoroughly to obtain component B; the concentration of GO@FE in component B is 1 mg / ml and the content of oxyhemoglobin HbO2 is 15 mg / ml, which is the same as that in component A.
[0064] (3) Mix component A and component B in a volume ratio of 1:1, let stand for 2 minutes. When there is no obvious flow on the gel surface and it does not slip when inverted, gelation is complete and gel OPQH / GO@FE is formed in situ.
[0065] Example 6: Preparation of a multifunctional injectable hydrogel
[0066] Unlike Example 5,
[0067] 1. Oxidized pullulan was prepared using the method described in the literature, as in Example 5.
[0068] 2. The oxyhemoglobin HbO2-PBS solution was prepared using the method described in the literature, as in Example 5.
[0069] 3. Assembly of OPQH / GO@FE injectable hydrogel
[0070] (1) Prepare an oxidized pullulan polysaccharide solution with a concentration of 20 mg / ml by preparing the oxidized pullulan polysaccharide in step 1, and add an appropriate amount of GO@FE prepared in Example 1 and HbO2-PBS solution prepared in step 2 of Example 5 to it and disperse it fully to obtain component A; the concentration of GO@FE in component A is 4 mg / ml and the content of oxyhemoglobin HbO2 is 20 mg / ml.
[0071] (2) Prepare a quaternized chitosan solution with a concentration of 90 mg / ml, add an appropriate amount of GO@FE prepared in Example 1 and HbO2-PBS solution prepared in step 2 of Example 5 to obtain component B; the concentration of GO@FE in component B is 4 mg / ml and the content of oxyhemoglobin HbO2 is 20 mg / ml, which is the same as that in component A.
[0072] (3) Mix component A and component B at a volume ratio of 2:1, let stand for 5 minutes. When there is no obvious flow on the gel surface and it does not slip when inverted, gelation is complete and gel OPQH / GO@FE is formed in situ.
[0073] Example 7: Preparation of a multifunctional injectable hydrogel
[0074] Unlike Example 5,
[0075] 1. Oxidized pullulan was prepared using the method described in the literature, as in Example 5.
[0076] 2. The oxyhemoglobin HbO2-PBS solution was prepared using the method described in the literature, as in Example 5.
[0077] 3. Assembly of OPQH / GO@FE injectable hydrogel
[0078] (1) Prepare an oxidized pullulan polysaccharide solution with a concentration of 30 mg / ml by dispersing an appropriate amount of GO@FE prepared in Example 1 and HbO2-PBS solution prepared in Step 2 of Example 5 into component A; wherein component A contains GO@FE The concentrations were all 3 mg / ml, and the content of oxyhemoglobin (HbO2) was all 17 mg / ml.
[0079] (2) Prepare a quaternized chitosan solution with a concentration of 30 mg / ml, add an appropriate amount of GO@FE prepared in Example 1 and HbO2-PBS solution prepared in step 2 of Example 5 to obtain component B; the concentration of GO@FE in component B is 3 mg / ml and the content of oxyhemoglobin HbO2 is 17 mg / ml, which is the same as that in component A.
[0080] (3) Mix component A and component B at a volume ratio of 1:2, let stand for 0.5 min, and when there is no obvious flow on the gel surface and it does not slip when inverted, the gelation is complete and gel OPQH / GO@FE is formed in situ.
[0081] Example 8: Partial performance characterization of the multifunctional injectable hydrogels prepared in Examples 5-7 (injectability, self-healing, oxygen release, and cfDNA removal)
[0082] This embodiment characterizes the OPQH / GO@FE gels prepared in Examples 5-7 for injectability, self-healing, oxygen release, and cfDNA clearance. The characterization results for the aforementioned properties are basically consistent with those of Examples 5-7. The following is a detailed explanation of the aforementioned performance characterization results, using Example 5 as an example.
[0083] 1. Injectable
[0084] Injectability test method: Components A and B of the OPQH / GO@FE gel prepared in Example 5 were mixed at a volume ratio and drawn into a 2 mL syringe. The mixture was then injected into deionized water through a needle. The continuity of extrusion and the presence of blockage or splashing were observed. Simultaneously, "NCUST" was written on a glass petri dish to assess the line continuity and moldability. The injectability and ease of operation of the hydrogel were comprehensively evaluated. For detailed results, see [link to results]. Figure 3 .
[0085] Figure 3 This visually demonstrates the excellent injectability of the hydrogel. For example... Figure 3 As shown, it can be easily extruded using a syringe ( Figure 3 b) and form a clearly identifiable “NCUST” logo. Figure 3 a) indicates that it has good plasticity and the ability to adapt to irregular wound surfaces.
[0086] 2. Self-healing properties
[0087] Self-healing test method: The self-healing properties of the OPQH / GO@FE gel prepared in Example 5 were evaluated by macroscopic observation and rheological analysis. (1) Macroscopic observation method: The gel was injected into the extended finger joint, and after shaping, it was divided, bent and contacted for 10 s, placed calmly for 2 min, and then bent again to observe the healing of the fracture surface. The results are detailed in […]. Figure 4 a. (2) Rheological analysis: 1% and 1000% strain were alternately scanned at 1 Hz (1% stress was applied from approximately 0-250s, 1000% stress from approximately 250-490s, 1% stress from approximately 490-740s, etc.). The changes in storage modulus G' (blue) and loss modulus G'' (red) with strain and time were recorded to evaluate the structural recovery and repair dynamics after network failure. The results are detailed in […]. Figure 4 b.
[0088] Figure 4 a represents the self-healing process of OPQH / GO@FE gel. For example... Figure 4 As shown in Figure a, (1) the original gel was intact and closely adhered to the finger; (2) after cutting, it was transformed into two completely separated gels; (3) thereafter, the two gels were placed together in contact; (4) after 1 minute, the gel was transformed back into an intact state; this shows that the OPQH / GO@FE gel prepared in Example 5 has excellent self-healing ability and can quickly form an intact shape after extrusion to fully fill irregular wounds.
[0089] Figure 4 b is a graph showing the elastic modulus of OPQH / GO@FE gel at 1% and 1000% strain. Figure 4As shown in Panel b, at 1% strain, the storage modulus G' (blue) is significantly higher than the loss modulus G'' (red); at 1000% strain, the loss modulus G'' (red) increases significantly, while the storage modulus G' (blue) decreases significantly to be lower than the loss modulus G'' (red). This indicates that the OPQH / GO@FE hydrogel presents a sol state (G′<G″) under 1000% high strain, and rapidly transforms into a gel state (G′>G″) after returning to low strain, and this reversible behavior remains consistent during multiple cycles; this indicates that the OPQH / GO@FE gel can recover rapidly after being damaged by high strain, which is consistent with Figure 4 the visual observation results of Panel a.
[0090] In conclusion, the OPQH / GO@FE gel prepared in Example 5 of the present application has excellent self-healing ability; this is because the dynamic Schiff base bonds break under high strain leading to network disintegration, and re-form under low strain to restore the network structure.
[0091] 3. Oxygen-releasing property
[0092] Determination method of oxygen-releasing capacity: place the OPQH / GO@FE gel (OPQH / GO@FE NIR(+)) prepared in Example 5 in PBS, and take the OPQH / GO@FE hydrogel without near-infrared irradiation (OPQH / GO@FE NIR(-)) and PBS as controls. Irradiate with 808 nm laser (1 W / cm²) for 10 min, then use a dissolved oxygen meter to determine the dissolved oxygen concentration of each group of samples before and after irradiation respectively, so as to evaluate the regulatory effect of laser on oxygen-releasing performance. In addition, perform five cycles of near-infrared light irradiation on the OPQH / GO@FE hydrogel, and record the oxygen release amount of each cycle to evaluate its cyclic oxygen release stability. Each experiment is repeated 3 times, and the results are shown in detail in Figure 5 Panel a and Figure 5b.
[0093] Figure 5 Panel a shows the oxygen-releasing capacity of PBS, OPQH / GO@FE NIR(-) and OPQH / GO@FE NIR(+) gels. As shown in Figure 5 Panel a, the dissolved oxygen concentration of the near-infrared irradiated OPQH / GO@FE hydrogel (NIR(+)) in deoxygenated PBS steadily rises to about 8.4 mg / L, while the PBS control group and the unirradiated group (NIR(-)) show no increase in oxygen concentration under the same conditions. This indicates that (1) the hemoglobin encapsulated in the hydrogel still maintains its biological activity of oxygen carrying and oxygen releasing, which confirms that the composite gel network effectively protects the hemoglobin activity; (2) the OPQH / GO@FE gel prepared in Example 5 has excellent oxygen-releasing capacity under light irradiation.
[0094] Further investigation was conducted on its cyclic oxygen release stability, Figure 5b represents the oxygen cycle release of the OPQH / GO@FE gel after five NIR irradiation switching cycles. For example... Figure 5 As shown in b, (1) oxygen release was detected in each of the five near-infrared on / off cycles, and (2) the total amount decreased slightly with the number of cycles (possibly due to the gradual consumption of hemoglobin or changes in the local microenvironment), but it was not completely inactivated. This indicates that the OPQH / GO@FE gel exhibits a stable and sustainable oxygen release capacity, which is of great significance for practical applications.
[0095] 4. Elimination of cfDNA
[0096] Method for cfDNA removal assay: To quantitatively evaluate the adsorption capacity of the hydrogel for cell-free DNA (cfDNA), the PicoGreen fluorescence method was used to quantify the concentration of remaining cfDNA. The experimental procedure is as follows: A 1 mg / mL stock solution (PBS, pH 7.4, stored at -20℃) was prepared using calf thymus DNA. Before the experiment, it was diluted to a working solution of 10 μg / mL with the appropriate buffer (pH 7.4 PBS, pH 5.8 PBS, or PBS containing 10% FBS). The PicoGreen working solution was diluted 1:200 with TE buffer and stored in the dark. Establishment of standard curve: 0–10 μg / mL DNA standards were prepared, and 100 μL of each was mixed with an equal volume of PicoGreen working solution. After reacting in the dark for 5 min, the fluorescence was measured (Ex / Em 485 / 525 nm). Take the hydrogel sample, add 4 mL of cfDNA working solution (gel:solution ≈ 1:10), incubate at 37℃ and 60 rpm for 24 h, centrifuge, collect 100 μL of the supernatant, and mix with an equal volume of PicoGreen working solution for fluorescence measurement. A blank control was set up to subtract the effects of DNA natural degradation; a background control (FBS solution + PicoGreen) was set up for the FBS-containing group to subtract background. The remaining cfDNA concentration was calculated from the standard curve, and the adsorption kinetic data are detailed in [link to data]. Figure 6 .
[0097] Figure 6The figure shows the cfDNA clearance rate of OPQH / GO@FE gel in different buffer solutions. As shown in Figure 6, the cfDNA clearance rate of OPQH / GO@FE hydrogel is similar at pH 7.4 and pH 5.8, indicating that the gel possesses pH-independent electrostatic adsorption properties. Notably, in the experiment at pH 5.8 with 10% FBS, FBS did not weaken its clearance ability but instead showed an auxiliary enhancing effect. The inventors believe that this may be because serum proteins in FBS may undergo conformational changes under acidic conditions, exposing hydrophobic regions or positively charged sites. On the one hand, these proteins form complexes with cfDNA, and on the other hand, they synergistically adsorb with quaternized chitosan, providing additional binding sites and thus promoting cfDNA capture. These results indicate that in the protein-rich acidic microenvironment simulating diabetic chronic wounds, OPQH / GO@FE gel can utilize serum components to achieve better cfDNA clearance, which helps to alleviate the inflammatory response.
[0098] Comparative Example 1: Preparation of OPQH / GO Injectable Hydrogel
[0099] Unlike Example 5,
[0100] 1. Oxidized pullulan was prepared using the method described in the literature, as in Example 5.
[0101] 2. The oxyhemoglobin HbO2-PBS solution was prepared using the method described in the literature, as in Example 5.
[0102] 3. Assembly of OPQH / GO injectable hydrogels
[0103] Both components A and B use unmodified graphene oxide (GO) at a concentration of 1 mg / ml (the same as the GO@FE concentration in Example 5). Components A and B are mixed at a volume ratio of 1:1 (the same as in Example 5), allowed to stand for 2 minutes, and gelation is complete when there is no obvious flow on the gel surface and it does not slip when inverted, forming an in-situ gel OPQH / GO.
[0104] Comparative Example 2: Preparation of OPQH Gel
[0105] Unlike Example 5,
[0106] 1. Oxidized pullulan was prepared using the method described in the literature, as in Example 5.
[0107] 2. The oxyhemoglobin HbO2-PBS solution was prepared using the method described in the literature, as in Example 5.
[0108] 3. OPQH Injectable Hydrogel Assembly
[0109] Both components A and B contain no modified / unmodified graphene oxide (GO). Components A and B are mixed at a volume ratio of 1:1 (same as in Example 5), allowed to stand for 2 minutes, and gelation is complete when there is no obvious flow on the gel surface and it does not slip when inverted, forming gel OPQH in situ.
[0110] Example 9: Partial property characterization of the injectable hydrogels prepared in Examples 5-7 and Comparative Examples 1-2 (gel-forming properties, morphology, modulus, antioxidant properties, photothermal properties, antibacterial properties, and biocompatibility).
[0111] This embodiment characterizes the injectable multifunctional hydrogel (OPQH / GO@FE) prepared in Examples 5-7, the OPQH / GO gel prepared in Comparative Example 1, and the OPQH gel prepared in Comparative Example 2. The results for the injectable multifunctional hydrogels prepared in Examples 5-7 of this application are consistent. The injectable multifunctional hydrogel (OPQH / GO@FE) prepared in Example 5 is described in detail below as an example. Meanwhile, the performance test results of the OPQH / GO gel prepared in Comparative Example 1 or the OPQH gel prepared in Example 2, which serve as controls, are also explained.
[0112] 1. Gel formation and pore structure
[0113] Figure 7 a represents the gelation diagram of OPQH gel, OPQH / GO gel, and OPQH@FE gel. (See diagram for example.) Figure 7 As shown in Example 5, Comparative Example 1, and Comparative Example 2, after mixing components A and B and letting stand for 2 minutes, there was no obvious flow on the gel surface and it did not slip when inverted, indicating that gelation was complete and rapid gelation was achieved in all cases.
[0114] The microstructure of the OPQH / GO@FE gel prepared in Example 5 was further observed using scanning electron microscopy (SEM), and the results are detailed in [link to SEM]. Figure 7 b. For example Figure 7 As shown in b, the OPQH / GO@FE gel exhibits an interconnected three-dimensional network structure with a uniform pore size distribution, and its average pore size is D = 109.98 ± 34.38 μm. This microstructure lays the foundation for the gel's oxygen release function.
[0115] 2. Characterization of storage modulus (G') and loss modulus (G'')
[0116] The storage modulus (G') and loss modulus (G'') of the injectable multifunctional hydrogel (OPQH / GO@FE) prepared in Example 5, the OPQH / GO gel prepared in Comparative Example 1, and the OPQH gel prepared in Comparative Example 2 were characterized. Specifically, the spectra of the storage modulus (G') and loss modulus (G'') as a function of strain were recorded at a constant frequency and a strain range of 1-1000%. The strain response characteristics of the hydrogels were analyzed, including the dependence of modulus on strain and the stability of the gel network structure. The results are detailed in […]. Figure 8 .
[0117] like Figure 8 As shown, (1) the OPQH gel prepared in Comparative Example 2 exhibits the highest storage modulus; (2) the OPQH / GO gel prepared in Comparative Example 1 has the lowest storage modulus; (3) the storage modulus of the OPQH / GO@FE hydrogel prepared in Example 5 is between that of OPQH / GO and OPQH / GO@FE. This indicates that when only GO is added, the mechanical strength of the hydrogel decreases. The inventors believe that this may be because GO disrupts the formation of Schiff base bonds, resulting in a reduction in the number of Schiff bases and a decrease in mechanical properties. However, when GO@FE (i.e., EGCG-Fe³⁺ modified GO) is added to the gel, the mechanical strength increases instead, producing an unexpected technical effect. The inventors speculate that this may be due to the ionic interactions and hydrogen bonding between EGCG and Fe³⁺ loaded on the surface of GO@FE and quaternized chitosan and oxidized pullulan, thereby effectively improving the mechanical properties of the hydrogel.
[0118] 3. Adhesion
[0119] Adhesion test method: The adhesion behavior of hydrogels to biological tissues was evaluated by macroscopic observation and overlap shear test. (1) Macroscopic analysis: OPQH / GO@FE was coated on the surface of pigskin and its adhesion stability under side and upside-down conditions was observed. The results are detailed in […]. Figure 9 a. (2) Quantitative analysis: Using pigskin strips (60 mm × 18 mm) as the substrate, with an overlap area of 18 mm × 18 mm, OPQH, OPQH / GO, and OPQH / GO@FE gels were coated. Shear loading was applied at 5 mm / min, the maximum load was recorded, and the adhesive strength was calculated. The adhesion properties of the three were compared. The results are detailed in [link to results]. Figure 9 b and 9c.
[0120] like Figure 9 As shown in Figure a, after the hydrogel was injected onto the surface of pigskin, it adhered firmly regardless of whether the pigskin was placed on its side or upside down. This demonstrates that macroscopic analysis validates the excellent adhesion properties of the OPQH / GO@FE gel.
[0121] like Figure 9As shown in b, compared with Comparative Examples 1 and 2, the OPQH / GO@FE gel group prepared in Example 5 exhibited the highest shear force and distance. The results, converted to adhesion strength, are as follows: Figure 9 As shown in c, the OPQH / GO@FE group had the highest adhesion strength (15.419 kPa), followed by the OPQH group (13.349 kPa), while the adhesion strength dropped to 12.05 kPa after adding graphene oxide (GO) alone. This indicates that adding GO actually reduced the adhesion performance of the hydrogel, while adding GO@FE significantly improved the adhesion performance of the hydrogel, producing an unexpected technical effect. The inventors believe that this may be due to the following reasons: (1) The carboxyl and hydroxyl groups on the surface of GO competitively react with the aldehyde group of oxidized pullulan or the amino group of quaternized chitosan, consuming the active groups used for tissue adhesion. (2) After EGCG-Fe³⁺ synergistic modification, the negative active sites on the surface of GO are shielded, reducing the consumption of adhesion groups by internal crosslinking. At the same time, non-covalent interactions such as metal coordination bonds, hydrogen bonds, and π-π stacking are introduced, enhancing the interfacial adhesion strength and toughness.
[0122] In summary, EGCG-Fe³⁺-modified GO (GO@FE) not only eliminates its negative impact on adhesion but also synergistically enhances the adhesion properties of hydrogels to biological tissues. This provides a mechanical and adhesive performance basis for its application in wound dressings, tissue sealants, and injectable bioadhesives, demonstrating significant technical effects and important practical application value.
[0123] 4. Antioxidant properties
[0124] Antioxidant performance determination method: The OPQH / GO@FE gel prepared in Example 5, the OPQH / GO gel prepared in Comparative Example 1, and the OPQH gel prepared in Comparative Example 2 were immersed in PBS at a ratio of 0.1 g / mL in pH 7.4 and extracted in a shaker at 37°C for 24 h. The supernatant was collected to obtain the gel extract. The scavenging rate of the extract against DPPH free radicals and hydroxyl free radicals was determined by the DPPH method and the Fenton method, respectively. Specifically, the extract was mixed with an equal volume of 0.1 mM DPPH working solution, incubated in the dark for 30 min, and the absorbance at 517 nm was measured. Separately, the extract was mixed with an equal volume of 9 mM FeSO4, 9 mM salicylic acid-ethanol, and 8.8 mM H2O2, reacted at 37°C for 30 min, and the absorbance at 510 nm was measured. The scavenging rate was calculated according to the formula. Each group was repeated three times. See the results for details. Figure 10 .
[0125] Figure 10 The scavenging rates of OPQH gel, OPQH / GO gel, and OPQH / GO@FE gel against DPPH (a) and hydroxyl radicals (b) are given. Figure 10 As shown, (1) the scavenging rates of DPPH and hydroxyl radicals of the OPQH gel prepared in Comparative Example 2 were 76.75% and 62.16%, respectively; (2) the scavenging rates of DPPH and hydroxyl radicals of the OPQH / GO gel prepared in Comparative Example 1 were 77.45% and 78.71%, respectively; and (3) the scavenging rates of DPPH and hydroxyl radicals of the OPQH / GO@FE hydrogel prepared in Example 5 were 84.92% and 97.05%, respectively, all significantly better than the OPQH and OPQH / GO groups. This indicates that the introduction of EGCG significantly enhances the antioxidant performance, which is attributed to the efficient donation of hydrogen atoms or electrons by the catechol and pyrogallol groups in the EGCG molecule to scavenge free radicals, and the EGCG-Fe³⁺ coordination network may synergistically stabilize the scavenging ability. Therefore, the OPQH / GO@FE hydrogel, with its excellent antioxidant activity, is expected to scavenge excess reactive oxygen species in the oxidative stress microenvironment of chronic diabetic wounds, reduce inflammation, and promote tissue repair.
[0126] 5. Photothermal properties
[0127] Photothermal Experiment Method: The OPQH / GO@FE gel prepared in Example 5, the OPQH / GO gel prepared in Comparative Example 1, the OPQH gel prepared in Comparative Example 2, and the blank control PBS were used as excitation sources. Temperature-time curves were measured for phosphate buffered solution (PBS), OPQH basic hydrogel, OPQH / GO composite hydrogel, and OPQH / GO@FE composite hydrogel to investigate the effect of different compositions on photothermal heating behavior. Results are detailed in [link to results]. Figure 11 a. Based on this, the photothermal stability and reusability of the OPQH / GO@FE hydrogel were further evaluated through a cycle experiment of five consecutive laser on-off cycles. The results are detailed in 11b.
[0128] Figure 11 a represents the photothermal curves of OPQH gel, OPQH / GO gel, OPQH / GO@FE gel, and PBS under NIR irradiation. Figure 11As shown in Figure a, under 10 min of near-infrared light irradiation at 808 nm and 1 W / cm², neither the PBS nor the OPQH gel showed a significant temperature increase. The OPQH / GO gel increased in temperature by approximately 6.8 °C, while the OPQH / GO@FE gel increased by approximately 11.9 °C, significantly higher than the OPQH / GO group. This indicates that although GO can improve the photothermal properties of the gel to some extent, the OPQH / GO@FE gel described in this application significantly enhances the light absorption and photothermal conversion efficiency of the hydrogel in the near-infrared region by employing GO@FE, achieving unexpected technical effects. This may be because the EGCG-Fe³⁺ complex may enhance the π-π stacking and nonradiative transitions of GO, thereby generating a more significant thermal effect and providing an ideal microenvironment for subsequent photothermal-triggered oxygen release.
[0129] Figure 11 b represents the photothermal stability of the OPQH / GO@FE gel after five NIR irradiation switching cycles. For example... Figure 11 As shown in b, (1) the OPQH / GO@FE gel maintains a consistent and repeatable heating effect during five consecutive on / off cycles, and (2) although the peak temperature is slightly reduced, it still has reliable photothermal stability. This indicates that the OPQH / GO@FE gel prepared in Example 5 of this application has good photostability and structural stability, is suitable for multiple or long-term photothermal modulation applications, and has important practical application value.
[0130] 6. Antibacterial properties
[0131] The antibacterial properties of the OPQH / GO@FE gel prepared in Example 5, the OPQH / GO gel prepared in Comparative Example 1, and the OPQH gel prepared in Comparative Example 2 were tested. The hydrogels prepared in Example 5 and Comparative Example 1 were divided into near-infrared light treatment groups, non-near-infrared light treatment groups, and a blank control group containing untreated bacteria. YPD liquid culture medium was prepared: 1.6 g of tryptone, 0.8 g of yeast extract, and 1.6 g of glucose were weighed, and deionized water was added to a final volume of 80 mL. The pH was adjusted to 7.0–7.4, and the medium was stirred until dissolved. For solid culture medium, 1.2 g of agar powder was added. The dispensing volume should not exceed 1 / 3–1 / 2 of the volume of the conical flask. Petri dishes, spreaders, sterile EP tubes, and pipette tips were prepared, and frozen Staphylococcus aureus and Escherichia coli bacterial suspensions were revived. All culture media and equipment in contact with the bacterial suspensions were autoclaved at 121°C for 15–20 min. Proper pretreatment is fundamental for the successful conduct of subsequent antibacterial experiments. For detailed results, see [link to results]. Figure 12 a and 12b.
[0132] Figure 12 a shows a plate photograph of typical agar cultures of Staphylococcus aureus and Escherichia coli in each group of gels and in the control group. Figure 12 b is Figure 12The survival rate of Staphylococcus aureus and Escherichia coli in a. Figure 12 As shown, (1) there was no significant difference in the effects of each gel group and the control group against Staphylococcus aureus; specifically, the OPQH / GO@FE gel described in this application showed no significant difference in antibacterial effect under near-infrared light irradiation compared to the no-light group, and both achieved a high level of antibacterial activity; (2) there was a significant difference in the effects of each gel group and the control group against Escherichia coli, with the antibacterial activity of the light-irradiated group (especially OPQH / GO@FE NIR(+)) being significantly enhanced, and the antibacterial rate of the OPQH / GO@FE gel described in this application being the highest. It is worth noting that this difference stems from the structural characteristics of the bacterial cell wall: Staphylococcus aureus has a thick and densely cross-linked cell wall, and is highly sensitive to the cation action of quaternized chitosan, so photothermal enhancement is limited; while Escherichia coli has a thin and loosely structured cell wall, and the photothermal effect of OPQH / GO@FE under NIR synergistically destroys the outer membrane, significantly enhancing the effect. The above results indicate that OPQH / GO@FE NIR(+) achieves enhanced clearance of Gram-negative bacteria through a photothermal-cationic-polyphenol synergistic mechanism; thus, the OPQH / GO@FE gel described in this application can provide an on-demand photothermal enhanced antibacterial strategy for infected wounds.
[0133] 7. Biosafety
[0134] The biocompatibility of the OPQH / GO@FE prepared in Example 5, the OPQH / GO gel prepared in Comparative Example 1, and the OPQH hydrogel prepared in Comparative Example 2 was determined by methods including blood compatibility, cytotoxicity, and cell viability / death staining.
[0135] (1) Blood compatibility assay: Following ISO 10993-4, OPQH / GO@FE, OPQH / GO, and OPQH gels were immersed in PBS at a ratio of 0.1 g / mL for 24 h at 37°C to obtain the extract. This extract was then mixed with an equal volume of 5% (v / v) rat erythrocyte suspension, incubated at 37°C for 1 h, and centrifuged. The absorbance at 545 nm was measured to calculate the hemolysis rate. Physiological saline and 10% Triton X-100 were used as negative and positive controls, respectively. Each group was repeated three times. See attached results. Figure 13 a and 13b.
[0136] Figure 13 'a' represents the color of the supernatant after centrifugation of each group of samples. For example... Figure 13As shown in Figure a, the supernatant of the positive control group (10% Triton X-100) was clear and bright red, indicating complete hemolysis; the supernatant of the negative control group (physiological saline) was clear and colorless, with intact red blood cell deposition. The supernatant color of OPQH hydrogel, OPQH / GO, and OPQH / GO@FE hydrogel was similar to that of the negative control group, being clear or very slightly pale pink, with tight and intact red blood cell sediment at the bottom of the tube, and no obvious hemoglobin release was observed. This indicates that the hemolysis test results showed that none of the hydrogels induced a significant hemolytic reaction, demonstrating good blood compatibility.
[0137] Figure 13 b is a comparison chart of the hemolysis rates of each group of samples. For example... Figure 13 As shown in b, the hemolysis rates of OPQH, OPQH / GO, and OPQH / GO@FE gels were all below 5%, far lower than that of 10% Triton X-100 (where all blood cells were destroyed), consistent with the results of macroscopic observation. This indicates that all gels exhibit good blood compatibility and have the potential for application in the treatment of diabetic ulcers.
[0138] (2) Cytotoxicity assay: The CCK-8 assay was used. OPQH gel, OPQH / GO gel, and OPQH / GO@FE extract were applied to HUVEC human umbilical vein endothelial cells, RAW264.7 macrophages, and L929 mouse fibroblasts at concentrations of 0.2, 0.6, and 1.0 mg / mL, respectively. Fresh culture medium was used as a control. Cell viability was calculated by measuring absorbance at 450 nm. See details for results. Figure 14 .
[0139] Figure 14 a represents the survival rate of HUVEC cells under 4-hour conditions for different concentrations of hydrogels. Figure 14 As shown in a, the HUVEC cell viability was higher than 80% at concentrations of OPQH, OPQH / GO, and OPQH / GO@FE gels in the range of 0.2–1 mg / ml. Figure 14 b represents the survival rate of L929 cells at different concentrations of hydrogels after 4 hours. Figure 14 As shown in b, except for the OPQH / GO gel at 1 mg / ml where the L929 cell survival rate was less than 80%, the L929 cell survival rate was higher than 80% for the other gel groups at 0.2-1 mg / ml. Figure 14 c represents the survival rate of RAW cells under 4-hour conditions for different concentrations of hydrogels. Figure 14 As shown in c, the RAW cell viability of OPQH, OPQH / GO, and OPQH / GO@FE gels was higher than 80% at concentrations of 0.2-1 mg / ml.
[0140] In summary, the OPQH gel, OPQH / GO gel, and OPQH / GO@FE gels, within the concentration range of 0.2–1.0 mg / mL, all exhibited survival rates higher than the 70% safety threshold specified in ISO 10993-5 against HUVEC human umbilical vein endothelial cells, RAW264.7 macrophages, and L929 fibroblasts. This indicates that none of the three gels exhibited significant cytotoxicity against either cell type within the measured concentration range.
[0141] (3) Cell viability and mortality assay: The Calcein-AM / PI double staining method was used. 0.2 mg / mL OPQH gel, OPQH / GO gel, and OPQH / GO@FE gel extract were co-cultured with HUVEC human umbilical vein endothelial cells, RAW264.7 macrophages, and L929 mouse fibroblasts for 3 days. After incubation in the dark with the staining working solution for 30 min, live cells (green) and dead cells (red) were observed under a fluorescence microscope. See attached results. Figure 15 .
[0142] Figure 15 Fluorescent images of HUVEC and L929 cells after live / dead staining using OPQH gel, OPQH / GO gel, and OPQH / GO@FE gel. Figure 15 As shown, in the fields of view of the three gels—OPQH gel, OPQH / GO gel, and OPQH / GO@FE—green fluorescence signals were dominant, with only a very few red dead cells observed; this indicates that all three gels have excellent cell compatibility, which is consistent with the CCK-8 results.
[0143] The above results demonstrate that the OPQH / GO@FE hydrogel prepared in Example 5 of this application has good blood compatibility and cell compatibility, meeting the basic safety requirements for in vivo application of biomedical materials.
[0144] In summary, the OPQH / GO@FE gel described in this application possesses the following excellent properties: (1) good plasticity and excellent self-healing ability, enabling it to quickly form a complete shape after extrusion to fully fill irregular wounds; (2) stable and sustainable oxygen release capacity; and (3) good blood compatibility and cell compatibility, meeting the safety requirements for in vivo application of biomedical materials. Furthermore, the OPQH / GO@FE gel described in this application is a Schiff base crosslinked hydrogel based on quaternized chitosan and oxidized pullulan, incorporating EGCG-Fe³⁺ modified graphene oxide (GO@FE) and oxyhemoglobin (HbO2). Compared to the OPQH / GO gel with GO, the OPQH / GO@FE gel described in this application not only achieves a significant improvement in mechanical strength and adhesion performance, resulting in significant technical effects, but also significantly enhances photothermal properties, making it suitable for multiple or long-term photothermal regulation applications. Simultaneously, through a photothermal-cationic-polyphenol synergistic mechanism, it achieves enhanced clearance of Gram-negative bacteria, improving antioxidant performance. Therefore, the OPQH / GO@FE gel described in this application achieves the synergistic integration of multiple functions such as cfDNA clearance, anti-oxidation, photothermal controlled oxygen release, and antibacterial properties, filling the gap in the existing technology for the joint regulation of multiple pathological disorders in diabetic chronic wounds. It has broad application prospects and important practical application value.
Claims
1. EGCG-Fe 3+ The application of modified graphene oxide in the preparation of multifunctional injectable hydrogels is characterized by: The injectable hydrogel is a Schiff base crosslinked hydrogel based on quaternized chitosan and oxidized pullulan.
2. The EG according to claim 1 C G-Fe 3+ The application of modified graphene oxide is characterized by: The multifunctional injectable hydrogel containing EGCG-Fe 3+ The content of modified graphene oxide is 0.9~4.0 mg / ml.
3. The EGCG-Fe according to claim 1 3+ The application of modified graphene oxide is characterized by: EGCG-Fe 3+ EGCG:Fe in modified graphene oxide 3+ The molar ratio of GO is 1:8:20~1:3:
7.
4. The EGCG-Fe according to any one of claims 1-3 3+ The application of modified graphene oxide is characterized by: The EGCG-Fe 3+ The modified graphene oxide was prepared by the following method: (1) a graphene oxide dispersion was prepared and ultrasonically dispersed; (2) under room temperature and light-protected conditions, EGCG was added and stirred until the modification was complete, then ferric chloride hexahydrate was added and stirred until the modification was complete. After centrifugation and washing, a precipitate was obtained, which was EGCG-Fe. 3+ Modified graphene oxide.
5. The EGCG-Fe according to claim 4 3+ The application of modified graphene oxide is characterized by: The concentration of the graphene oxide dispersion in step (1) is 0.05-0.3 mg / ml; the ultrasonic dispersion treatment is specifically performed by ultrasonic cleaning in a 40 Hz ultrasonic cleaner for 25-50 min; the stirring time after adding EGCG in step (2) is 25-45 min, the stirring time after adding ferric chloride hexahydrate is 2-5 min, and the centrifugation treatment is specifically performed by centrifugation at 2-8℃ and 12000-13000 r for 5-10 min.
6. A multifunctional injectable hydrogel based on any one of claims 1-5, wherein the injectable hydrogel is a Schiff base crosslinked hydrogel of quaternized chitosan and oxidized pullulan, characterized in that: The injectable hydrogel also includes EGCG-Fe 3+ Modified graphene oxide GO@FE and oxyhemoglobin HbO2; wherein the content of GO@FE is 0.9-4 mg / ml and the content of oxyhemoglobin HbO2 is 14.5-20 mg / ml.
7. The multifunctional injectable hydrogel according to claim 6, characterized in that: The Schiff base crosslinked hydrogel is obtained by reacting a quaternized chitosan solution and an oxidized pullulan solution at a volume ratio of 2:1 to 1:2; the concentration of the oxidized pullulan solution is 20-40 mg / ml, and the concentration of the quaternized chitosan solution is 30-90 mg / ml.
8. The multifunctional injectable hydrogel according to claim 6 or 7, characterized in that: The quaternized chitosan solution and / or oxidized pullulan polysaccharide solution contain appropriate amounts of graphene oxide GO@FE and / or oxyhemoglobin HbO2.
9. The method for preparing the multifunctional injectable hydrogel according to any one of claims 6-8, characterized in that: Includes the following steps: (1) Prepare an oxidized pullulan polysaccharide solution with a concentration of 20-40 mg / ml, add an appropriate amount of GO@FE and HbO2 in PBS solution to obtain component A; (2) Prepare a quaternized chitosan solution with a concentration of 30-90 mg / ml, add an appropriate amount of GO@FE and HbO2 in PBS solution to obtain component B; (3) Mix component A and component B in a volume ratio of 2:1 to 1:2, let stand for 0.5 to 5 minutes, and form gel OPQH / GO@FE in situ.
10. The method for preparing the multifunctional injectable hydrogel as described in claim 9, characterized in that: The concentration of GO@FE in both components A and B is 0.9-4.0 mg / ml, and the content of oxyhemoglobin (HbO2) is 14.5-20 mg / ml.